Desempenho e emissões de motor agrícola ciclo diesel utilizando diferentes combustíveis - Perin, Gismael Francisco (2014)
The behavior of the agricultural cycle diesel engine when changes the fuel type and operating mode, must be known so that we can identify the best fuel resulting in better performance at lower emissions. However, when using particular type of fuel, with or without blends, the motor parameters such as torque, power and consumption, and emissions of gases changes. Therefore, the aim of this work was to verify the influence of the types of fuels for performance parameters of the agricultural cycle diesel engines and the emissions generated by burning fossil fuels. For this first experiment was conducted to determine the ideal number of repetitions and the warming s time the engine to perform the experiments proposed by objectives. Eighteen repeticions were conducted in 3 groups corresponding to warm times of 20, 60 and 100 minutes. To identify whether there was a significant difference between the warming s time was conducted the analysis of variance and the minimum number of repetitions required was identified by a lower rate of coefficient of variation. The experimental performance of the engine with different fuels was performed using 11 fuel (Diesel S10, S500 diesel, biodiesel and its blends [5%, 10%, 15%, 20%, 50% and 100% concentration of biodiesel in diesel]). Outcome variables were assessed torque, power consumption and time specific consumption. Analysis of variance was performed and, if present difference, the data were subjected to the mean comparison test (Tukey p ≥ 0.05) and linear regression analysis. Emissions of O2, CO2, NO2, NO, CO and HC were analyzed. The fuels used were the same performance experiment with the same blends. The emissions test followed the methodology laid down in the NBR ISO 8174-4:2012, which indicates 8 modes of operation of the engine in three rotations. Analysis of variance was performed and, if present difference, the data were subjected to the mean comparison test (Tukey p 0.05) and linear regression analysis. The results report that four were the number of repetitions for the test performance and that 20 minutes was the time of warming the engine. Both the type of fuel and the operating mode significantly alter the performance and emissions. There was a reduction of the maximum torque and maximum power and increased consumption and minimum specific consumption with increase of biodiesel in the blend. Emissions of NO2 and O2 increased with higher concentration of biodiesel in the blend. Emissions of CO2, opacity, NO, CO and HC were decreased as increasing the amount of biodiesel in the blend with mineral diesel. In all variables, except O2, there was a reduction in emissions decreased when the load applied in engine. The fuel reduced emissions and maintained performance, compared with commercial diesel fuel was Diesel S10 with 20% biodiesel.